Pengaruh Penerapan Coi Framework pada Pembelajaran Online Terhadap Peningkatan Pemahaman (Subkategori Cognitive Presence) Mahasiswa - Asalla, Lydiawati Kosasih; Maria, Naova; Hannesto, Rainer (Bina Nusantara University, 2014)
This study aims to discuss some of considerations in education to achieve good quality in learning instruction. The indicator is student’s comprehension increasing through the use of technological advances such as electronic learning (E-Learning) on social media and using Community of Inquiry (CoI) model as a comparative study to improve the quality of E-Learning program. The data used in this study were obtained through survey to intended students and literature study. Final conclusion of this study is a proposal to teachers on an interactive learning and rich of knowledge that will improve the learner’s comprehension.